2008
DOI: 10.1007/s10236-008-0141-x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impact on extreme wave conditions in the North Sea: an ensemble study

Abstract: An analysis of today's mean and extreme wave conditions in the North Sea and their possible future changes due to anthropogenic climate change are presented. The sea state was simulated for the 30-year period 2071-2100 using the wave model WAM and an ensemble of wind field data sets for four climate change realizations as driving data. The wind field data sets are based on simulation outputs from two global circulation models (GCMs: HadAM3H and ECHAM4/ OPYC3) for two emission scenarios (A2 and B2, Intergovernm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
95
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(103 citation statements)
references
References 22 publications
7
95
0
1
Order By: Relevance
“…This was also described by Groll et al (2014). Both Debernard and Røed (2008) and Grabemann and Weisse (2008) reported that model-induced uncertainties and inter-GCM variability are larger than the scenario-related uncertainties ( Fig. 6.7).…”
Section: Future Changes In Wavessupporting
confidence: 55%
See 2 more Smart Citations
“…This was also described by Groll et al (2014). Both Debernard and Røed (2008) and Grabemann and Weisse (2008) reported that model-induced uncertainties and inter-GCM variability are larger than the scenario-related uncertainties ( Fig. 6.7).…”
Section: Future Changes In Wavessupporting
confidence: 55%
“…The authors compared the results of the 30-year time slices for 1961-1990 (reference climate) and 2071-2100 (future climate) and found changes in the wave conditions for the four climate projections to vary in their spatial pattern and magnitude but that all agree in an increase of severe significant wave heights (99th percentiles) of 6-8 % along the North Sea east coast and in the Skagerrak. Grabemann and Weisse (2008) found comparable changes using a slightly different set of four climate projections, which incorporates two GCMs and SRES scenarios A2 and B2. Comparing the time slices 1961-1990 and 2071-2100 they estimated an increase in extreme wave height (99th percentile) in large parts of the southern and eastern North Sea of about 5-8 % (25-35 cm, average for the four projections).…”
Section: Future Changes In Wavesmentioning
confidence: 92%
See 1 more Smart Citation
“…For the coast of the Wadden Sea, Katsman et al (2011) estimate a regional sea level rise of 0.40-1.05 m by 2100. Additionally, the North Sea coastal areas are also exposed to significant and increasing storm events (Beniston et al, 2007;Grabemann and Weisse, 2008;Nicholls et al, 2007;Woth et al, 2005) and shifts in precipitation's scale and time (Beniston et al, 2007;Jacob et al, 2008;Spekat et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The climate scenario is obviously important, and only two future scenarios are considered in this study. However, studies have demonstrated that the choice of climate model might contribute more to the overall uncertainty of the future wave climate than the climate scenarios themselves (Wang and Swail 2006;Grabemann and Weisse 2008;Grabemann et al 2015;Wang et al 2012Wang et al , 2014see also de Winter et al 2013). Future projections of waves are typically obtained using wind output from climate models as input to numerical wave models, and also the choice of wave model, the downscaling method and the model resolution will have a big impact on the results.…”
Section: Introductionmentioning
confidence: 99%